Archaeochionelasmus nekvasilovae gen. et sp. nov. (Cirripedia, Balanomorpha, Chionelasmatoidea) from the Bohemian Cretaceous Basin (Czech Republic): the first bona fide Cretaceous neobalanoform - Kočí, Tomáš; Veselská, Martina Kočová; Newman, William A.; Buckeridge, John S.; Sklenář, Jan (Zootaxa, 2017)
This paper records a new sessile cirripede from a nearshore, shallow-water facies at Předboj near Prague, Czech Republic. The new taxon, Archaeochionelasmus nekvasilovae gen. et sp. nov., is the earliest known neobalanoform barnacle, and while it may have been an obligate commensal of a cephalopod or marine reptile, that it was a shore barnacle cannot be ruled out. (Zoobank registration: urn:lsid:zoobank.org:pub:177CC951-CEC1-425C-B693-46ADB83BD5D9)